RUANG LINGKUP PENDIDIKAN ISLAM KONTEMPORER - Ahmad Sahiba (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
As a agent of change, an Islamic education is required to play a role in a dynamic and proactive. Among the major issues entanglement, he also confronted the challenges and prospects for the future. The development of intellectual creative insight and dynamic in various fields in the broadcast and integrated with Islam, is a major aspect that should be implemented, both in the realm of theory and praxis. In this discussion, we discuss some issues related to Islamic education contemporer in the globalization era that aims to find out more about the problem of Islamic education, discusses the challenges of Islamic education in the globalization era, and to know how big the role of Islamic education in the era of globalization. So in essence there are several solutions for the advancement of education in the contemporary Islamic include: immediately realized the community / communities Islamic education of professionals, both theoretically and practitioners of Islamic education, creating a condusif culture to be able to give birth again Muslim intellectuals that are reliable, conducting intensive dialogue, develop study models of education that is able to open dialogue with outside elements, and able to integrate Islamic values into the education system.